2015
DOI: 10.17221/8383-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and amphetamine-regulated transcript immunoreactive nerve fibres in the mucosal layer of the canine gastrointestinal tract under physiological conditions and in inflammatory bowel disease

Abstract: ABSTRACT:The objective of this study was to determine the effect of canine inflammatory bowel disease (IBD) on the density of cocaine-and amphetamine-regulated transcript (CART) immunoreactive nerve fibres in the mucosa of different sections of the gastrointestinal tract. Fibre density was analysed in mucosal specimens from the duodenum, jejunum and descending colon of healthy dogs and patients with inflammatory bowel disease of varying intensity. Nervous fibres were stained in single-cell immunofluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…The results of Q-PCR technique obtained in the present experiment demonstrated for the first time the presence of mRNA encoding CART in the stomach of healthy pigs, complementing the existing and only immunocytochemical data on its expression in the gastrointestinal tract of this species [ 11 , 12 , 31 , 34 , 40 ]. Since different mechanisms are engaged in the regulation of mRNA expression and final peptide abundance, the results of Q-PCR technique and immunohistochemistry may vary in the same tissues [ 44 ].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of Q-PCR technique obtained in the present experiment demonstrated for the first time the presence of mRNA encoding CART in the stomach of healthy pigs, complementing the existing and only immunocytochemical data on its expression in the gastrointestinal tract of this species [ 11 , 12 , 31 , 34 , 40 ]. Since different mechanisms are engaged in the regulation of mRNA expression and final peptide abundance, the results of Q-PCR technique and immunohistochemistry may vary in the same tissues [ 44 ].…”
Section: Discussionsupporting
confidence: 79%
“…In healthy animals, singular, irregularly arranged submucosal CART-immunoreactive gastric perikarya were observed only in sporadic studies (present study; [12,32,39]) or were completely absent [11,31,34,40] suggesting their minor importance for intramural regulation of the stomach mucosa secretory function. The reasonable explanation for the abovementioned minor variations presented by different authors seem to result from tissue sampling differences, as described before.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Moreover, it cannot be excluded that CART in neuronal structures of the gallbladder may act (like in the central nervous system) as an endogenous antioxidant and exhibits neuroprotective and neurotrophic effects, especially during neuronal cells injury [2,24,27,43]. It is all the more probable that relatively large number of previous studies showed the changes in the number of CART-positive enteric nervous during a wide range of intestinal and extra-intestinal processes [15,21,33], and such fluctuations were also noted during the present study.…”
Section: Discussionmentioning
confidence: 99%